Actividad de ATP asa en corazón de cobayos de altura - Oyola H., Luz (2004)
Heart rnitochondrion ATPase activity, ADP:O ratio (P:O) and Respiratory Control (RCR) are compared between guinea pigs from high altitude (Morococha, 4540 m) (HA) and those from sea level (SL). The study comprised 60 male guinea pigs, 30 from each altitude level, with mean weight 400-450 grams. Heart mitochondria were obtained by differential centrifugation at 4°C. P:O ratio and RCR were measured polarographically by Tyler method, and ATP hydrolysis was done by Holton et al. Method. Mean values obtained for heart mitochondria at SL and HA, expressed in mmoles oxygen uptake/mg protein/hour, were, with Glutamate + Malate as subtrates, respectiveIy: P:O 2.90, RCR 6.02 and P:O 2.93, RCR 6.0; and, with Pyruvate + Malate as subtrates, respectively P:O 2.60, RCR 5.0 and P:O 2.70, RCR 4.80. ATPase activity was at SL and HA, respectively: 57.50 and 64.50 mmoles P /mg protein/hour. The results suggest that high altitude guinea pigs may have developed the ability to perform oxydative phosphorylation more efficiently, and that the slight increment observed in ATPase activity indicates that some adjustments are made to maintain the equilibrium within the mitochondrial environment.